Carbonate pore type classification by using digital rock images with a rock physics model, offshore Sarawak - Lubis, L.A. (European Association of Geoscientists and Engineers, EAGE, 2014)
It has been documented that Carbonate contributes the most hydrocarbon resources worldwide. For rigorous reservoir characterization and performance prediction from seismic, the exact interpretation of geophysical response of different Carbonate pore types is crucial. Yet, the characterization of Carbonate reservoir rocks is difficult due to their complexity. Unlike clastics, diagenesis also plays a strong role in this classification. Therefore, it is difficult to establish rock physics model for Carbonate. We evaluate the possible rock physics model of twenty core plugs of a Miocene Carbonate platform in Central Luconia, Sarawak. The published laboratory data of this area were used as input to create the models. The elastic properties were analyzed to examine the validity of an existing analytical Carbonate rock physics model. We integrated the Differential Effective Medium Model and the elastic modulus which was simulated from a digital Carbonate rock image. The results matched well for the separation of Carbonate pore types and sonic velocity obtained from laboratory measurement. Thus, the results of this study show that the integration of rock digital image and theoretical rock physics have the scope to improve the elastic properties prediction and as an input for more advance Seismic Inversion of Carbonate reservoir in Sarawak.